Utilization of an NNSS receiver in the explosion seismic experiments on the Prince Olav Coast, East Antarctica 2. Positioning - Kazuo Shibuya; Kiyoshi Ito; Katsutada Kaminuma (National Institute of Polar Research, 1982)
Performance tests of a one-wave (400MHz) NNSS receiver and a two-wave (150 MHz and 400 MHz) NNSS receiver were made at Syowa Station, East Antarctica. The two-dimensional positioning by a one-wave receiver scattered with the standard deviation of about 200m from the mean position determined by many passes. The two-dimensional positioning by the two-wave receiver scattered with the standard deviation of 25m for the latitudinal direction and 50m for the longitudinal direction, respectively. The mean position by many passes by the one-wave receiver and that by the two-wave receiver were relatively located within 70-80m. Three-dimensional positioning was made by accumulating doppler data of several passes and the estimate of convergence was made by taking the number of satellite passes as a parameter. Probable error in two-dimensional co-ordinates was shown to reduce from 60m to 40m, 20m and further to 10m according as the pass number was increased from 3 to 7,15 and further to 25. The corresponding height error reduced from 20m to 10m and further to 5m according as the pass number was increased from 3 to 7-15 and further to 25. There is a difference of about 370-400m between the positioning by the satellite fixing on the WGS-72 earth ellipsoid and that by an astronomical observation. There is also the difference of 30±2m between the antenna height and the elevation from the mean sea level at the same point. In the explosion seismic experiments by the 21st Japanese Antartic Research Expedition, three-dimensional positioning of most of the seismic stations was made within 15 days by receiving 3-25 passes at each station. There remained the difference of 20-40m between the antenna height and the elevation for most of the seismic stations. The difference between the antenna height and the elevation gives the approximate geoid height, and the obtained values in this region of Prince Olav Coast are consistent with the geoid map obtained by the SEASAT altimetry data. In order to obtain the convergent procedures better ...